Patient Preferences for Nonvitamin K Antagonist Oral Anticoagulants in Stroke Prevention: A Multicountry Discrete Choice Experiment - Thomas Wilke; Anna-Katharina Meinecke; Bernhard Schaefer; Sandra Buchwald; Daniel Eriksson; Sabrina Müller (Cardiology Research and Practice, 2019)
Purpose. The patient’s perspective is becoming increasingly important in clinical and policy decisions. This study examined atrial fibrillation (AF) patient preferences for different characteristics of nonvitamin K antagonist oral anticoagulants (NOACs). Methods. A discrete choice experiment (DCE) addressing AF patients treated with NOACs in France, Germany, and the United Kingdom was conducted. The DCE included the following attributes: frequency of administration (once/twice daily), size of tablet/capsule (6–9 mm/20 mm), meal-related intake (intake with food required/independent), and distance to treating physician (1 km/10 km). Preferences were analyzed based on a conditional logit regression model. Results. In total, 758 patients (males: 57.3%; mean age: 71.4 years) with an average disease duration of 5.5 years were included (apixaban/dabigatran/edoxaban/rivaroxaban: 34.0%/14.5%/6.6%/44.9%, respectively). Patients preferred NOAC treatment options characterized by once-daily dosing regimens (42.8%; p<0.001), shorter distance to treating physicians (25.0%; p<0.001), a small-sized tablet (21.5%; p<0.001), and intake independent of food (10.6%; p<0.001). Conclusions. Patients primarily prefer a once-daily NOAC regimen. Individual preferences should be considered for the treatment of AF patients as this may result in improved treatment adherence and consequently better effectiveness and safety in routine clinical practice.